From Epigraphy to Historical Tourism: The Talang Tuo Inscription's Potential as a Heritage Tourism Resource in the Sriwijaya Kingdom - Tomy Wijaya; Fatimah Alauwiyah; Syarifuddin Syarifuddin; Alif Bahtiar Pamulaan (MASI Mandiri Edukasi, 2025)
This study examines the historical and cultural importance of the Talang Tuo Inscription and its potential as a heritage tourism resource in South Sumatra. Prior studies have predominantly concentrated on its philological and religious dimensions, resulting in a deficiency in comprehending its significance for cultural heritage management and sustainable tourism development. Commissioned by Dapunta Hyang Sri Jayanasa in 684 AD, the inscription encapsulates Sriwijaya’s ethical, spiritual, ecological, and humanitarian perspective, highlighting welfare, social cohesion, and equilibrium with nature. This study utilizes the historical method, incorporating heuristics, source criticism, interpretation, and historiography, and is based on inscription analysis, literature review, and field observations conducted at the Balaputera Dewa Museum. The findings indicate that the inscription served not only as an administrative record but also as a political and cultural manifesto that defined Sriwijaya’s identity as an ethical and ecological civilization. Currently, it has significant potential to advance heritage tourism through digital integration (AR/VR), site collaboration, and community-based management. This study emphasizes the need to convert the Talang Tuo Inscription into dynamic heritage, to enhance cultural diplomacy and sustainable heritage tourism, and to present a novel framework that amalgamates historical analysis with cultural tourism planning.